2006
DOI: 10.1038/sj.ijo.0803264
|View full text |Cite
|
Sign up to set email alerts
|

Cellular adhesion molecules and their relationship with measures of obesity and metabolic syndrome in a multiethnic population

Abstract: Background:The relationships between adhesion molecules and measures of obesity and metabolic syndrome in different ethnic populations are unclear. Objective: Our aim was to study the association between body mass index (BMI), waist-hip ratio (WHR) and the parameters of the metabolic syndrome with four different adhesion molecules, adjusting for potential confounders, in men and women from different ethnic origins. Methods: Soluble plasma adhesion molecules (sP-selectin, sE-selectin, intracellular adhesion mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
7
29
3
Order By: Relevance
“…A high level of inflammation (assessed by hs-CRP) in hypertensive patients with acute ischemic stroke has been linked to an increased risk of future cardiovascular mortality [34]. A study on normotensive subjects revealed that adhesion molecules, particularly the sE-selectin, relates to obesity (waist and hip ratio), whereas the relationship between adhesion molecules and BP in hypertensive subjects is adhesion molecule-specific and varies with sex and age, which may partially explain inconsistencies found in the literature [35].…”
Section: Multivariate Analysis Of the Effects Of Vitamin Supplementatmentioning
confidence: 72%
“…A high level of inflammation (assessed by hs-CRP) in hypertensive patients with acute ischemic stroke has been linked to an increased risk of future cardiovascular mortality [34]. A study on normotensive subjects revealed that adhesion molecules, particularly the sE-selectin, relates to obesity (waist and hip ratio), whereas the relationship between adhesion molecules and BP in hypertensive subjects is adhesion molecule-specific and varies with sex and age, which may partially explain inconsistencies found in the literature [35].…”
Section: Multivariate Analysis Of the Effects Of Vitamin Supplementatmentioning
confidence: 72%
“…Finally, leukocytes infiltrate the extravascular space via PECAM-1. There is a good body of evidence showing increased levels of serum-soluble adhesion molecules, including soluble ICAM-1, VCAM-1, P-selectin, and E-selectin, in obese populations (11), and obesity is also associated with persistent platelet activation (12). These data suggest that obese adipose tissue is a site of enhanced interaction between ECs and leukocytes.…”
Section: Introductionmentioning
confidence: 92%
“…In older adults elevated D-dimer levels accompany insulin resistance (16). In middle-aged adults sICAM-1 has been shown to be associated with insulin resistance (17), although other studies show no such association (18).…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The primary data analytical approaches included Pearson correlation and multiple linear regression.…”
mentioning
confidence: 99%